PEMENUHAN HAK KESEHATAN REPRODUKSI NAPI PEREMPUAN DI LEMBAGA PERMASYARAKATAN (LAPAS) PROVINSI RIAU - Achmad Hidir; Rr Sri Kartikowati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
It is suspected that there is a potential human rights abused against woman prisoner’s reproductive health in Riau Province’s prisons. This research aims to identify human rights abused related woman prisoner’s reproductive health and found the affort to reduce it. The methods used to collect the data are interviews, documentation and observation. While Focus Group Discussion (FGD) conducted as part of the analysis stage interactive model (Miles and Huberman). The results showed that there is a potential human rights abused related to woman prisoner’s reproductive health in Riau Province prisons. It is occurred because of limited prison infrastructure, including getting access to goods essential needs during menstruation like pads. Efforts to reduce human rights abused against women prisoners in the prisons while improving compliance and protection of human rights is conducting the capacity building for the staff of prisons, setting clear standards compliance for the health rights of women prisoners, operating system of evaluation and monitoring of the implementation of the health right, adding women prisons officers, and build prisons that were intended for female inmates.